Practitioner's complete guide to M&As an all-inclusive reference - Emott, David T., 1944- (Wiley finance series, 2011)
"The ultimate guide to the ins and out of mergers and acquisitions Practitioner's Complete Guide to M&As provides the practical tricks of the trade on M&As: what they need to know, what they have to know, and what they need to do. Numerous examples and forms are included illustrating concepts in discussion. Written in a straight-talking style. A highly, practical application-oriented guide to mergers and acquisitions. Covers strategy development; deal flow and target identification; due diligence; valuation and offers; tax structuring; negotiation; and integration and value creation". Presents information using bullet points rather than lengthy narrative for ease of reading. Numerous exhibits, forms, and examples are included. This practical guide takes you through every step of the M&A process, providing all the necessary tools that both the first-time M&A player as well as the seasoned practitioner need to complete a smart transaction."--